NELA.01The Impact of Laparoscopy on Emergency Surgery for Adhesional Small Bowel Obstruction: Prospective Single Centre Cohort Study. (28th October 2021) - Darbyshire, Alexander; Kostakis, Ina; Pucher, Phil; Toh, Simon; Mercer, Stuart
Abstract: Aims: Laparoscopic adhesiolysis is being increasingly used to treat adhesional small bowel obstruction (ASBO). However, concerns regarding iatrogenic bowel injury and failure to relieve the obstruction have limited its uptake. This study reports our centre's experience of adopting laparoscopy as the standard operative approach for ASBO. Methods: A single centre prospective cohort study was performed incorporating local data from the National Emergency Laparotomy Audit Database; 01/01/2015-31/12/2019. All patients undergoing surgery for ASBO were included. Patient demographic, operative and in-hospital outcome data were compared between different surgical approaches. Linear regression analysis was performed for length of stay. Results: Of 299 cases, 76.3% were started laparoscopically and 52.2% successfully completed. Rates of attempted laparoscopy increased over the 5 year period. Patients treated laparoscopically had lower P-POSSUM-mortality (2.1 vs 5.7%, p = <0.001), shorter post-operative LOS (4.2 vs 11.3 days, p = 0.000) and lower in-hospital mortality (2 vs 7 deaths, p = <0.001). In regression analysis, laparoscopy had the strongest association with post-operative LOS ( 8.51, p = 0.002). Conclusion: Laparoscopy is a safe and feasible approach for adhesiolysis in the majority of patients with ASBO. It is now the standard approach in our centre, with 83.3% of cases started laparoscopically in 2019. It is associated with reduced post-operative length of stay with no impact on complications or mortality. This challenges the widely held view that laparoscopy should be for selected, straightforward cases.